PEMBUATAN SILIKA TERMODIFIKASI DARI SEKAM PADI SEBAGAI ADSORBEN LOGAM BERAT PADA LIMBAH CAIR [REVIEW] - Oktavia Safitri; Harun Alrasyid; Kartika Udyani (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
ABSTRACT Some heavy metals that can pollute the environment and are toxic are lead [Pb], nickel [Ni]. Waste water treatment that contains heavy metals can be done by the adsorption method, because it is more efficient and economical. The review discusses how to determine the use of rice husks as heavy metal adsorbents in liquid waste and how to modify silica rice husks as adsorbents in order to increase the ability of absorption of heavy metals in liquid waste. In this stage the method of rice husk silica by means of rice husk is heated by heating around 7500C and the rice husk silica is modified with solutions such as 3-aminopropyl trimethoxysilane. From this literature study can provide information about the adsorption power of modified rice husk silica to heavy metals in liquid waste. The order maksimum of Pb, and Ni is 98,14% absorption efficiency and 99.43% Keywords : waste water, heavy metals, silica, rice husk, adsorption